Diagnosis of rheumatoid arthritis of the shoulder joint - Gerasimenko, Sergey; Babko, Andrey; Poluliakh, Mykhaylo (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
The article describes objective mechanisms in the formation of the shoulder joint contractures in patients with rheumatoid arthritis at different stages of the pathological process. Clinical, instrumental and laboratory methods of examination made it possible to detect the extent of damaging of the osseous and soft-tissue structures in the shoulder joint region, this extent influencing the tactics of treatment for such patients.